Islamic Transformation Centre and the Quadruple Helix Model (QHM) collaboration: empowering disabled students through inclusive education - Md., Habibullah; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2015)
Inclusive education emerged by insisting that children with special need to be included in the traditional classroom. The purpose of this paper is to propose the Islamic Transformation Centre (ITC), for inclusive education. This paper reviews the literature and adopts the Business Model Canvas (BMC) to propose the conceptual solution for inclusive education. The conceptual solution will be implemented through the use of Islamic Transformation Centre (ITC) with the collaboration of Ministry of Education (MoE) and other Quintuple Helix Model actors i.e. University, Industry, and Citizen/NGOs. It is hoped that this paper will not only generate discussion but also interest that will lead to the development of the right spirit for the promotion of effective inclusive education.